University extension project in a community of elderly people in São Paulo during the COVID-19 pandemic: experiences (PerCursos, 2023)
This article seeks to present the experiences of a group of 48 undergraduates from the areas of nursing, medicine, nutrition, and psychology at a University Center, located in the city of São Paulo, alongside a basic social protection equipment aimed at elderly people in vulnerable social situations. These students were part of a university extension project that seeks to encourage innovation, respect for diversity, and reinforce interdisciplinary and interprofessional work through the building of a social project focused on the needs of the target population. One of the lines of work of the project is aimed at the elderly population. The project was developed during the COVID-19 pandemic, from 2020 to 2022. For these undergraduates, listening to the life stories of another group of people and being able to live with them in a semi-professional way, showed them the importance of respect, listening and empathy. It was clear to the group of students the autonomy of said elderly and how negative stereotypes can limit it. It is considered that the project contributes to the consolidation not only of the process of learning, but, above all, with a return of this learning to society. It is believed that the contribution is not only in the now, but also future, as it brings important reflections to these future professionals about the multiplicity of aging and its possibilities, social inequalities, and the alternatives of work beyond the hospital environment, in a more humanistic and critical way.
Keywords: aged; universities; medical education; older people; humanization of assistence; universities and colleges